In Vitro Anti-Microbial Activity of Aqueous and Ethanolic Leaf Extracts of Justicia flava and Tephrosia vogelii that grows in Uganda. - Masete, George Alfred (Student’s Journal of Health Research Africa, 2021)
Background: Medicinal plants and plant-derived medicines are increasingly becoming popular in modern society as natural alternatives to synthetic chemicals due to increased resistance to drugs by microbes. There is a need to search for new active compounds to validate the medicines used traditionally. The study was carried out on the aqueous and ethanolic leaf extracts of Justicia flava and Tephrosia vogeli, to determine their antimicrobial and phytochemical profiles. Method The agar well diffusion method using Mueller Hinton agar plates, to determine the diameters of the antibacterial inhibition zones of the ethanolic and aqueous extracts on standard bacterial strains of Staphylococcus aureus, Pseudomonas aeruginosa, and Salmonella spp was conducted. Results Ethanol extract of Justicia flava showed activity against S. aureus and P. aeruginosa and no activity on Salmonella spp. The aqueous extract had no activity on any of the three bacteria. However, both the aqueous and ethanol extract of T. vogelii showed activity on the test microbes used, and the highest activity was seen with Salmonella spp. For minimum inhibitory concentration (MIC), J. flava, P. aeruginosa had the highest value of 500mg/ml and S. aureus showed the lowest value of 250mg/ml whereas, with the aqueous extract of T. vogelii, P. aeruginosa showed the highest MIC value of 165mg/ml and Salmonella spp the lowest of 41.25mg/ml. However, Salmonella showed a high value (300mg/ml) with the ethanol extract and S. aureus the lowest (75mg/ml). The phytochemical screening revealed the presence of saponins, terpenoids, tannins, phenolics, and reducing sugars. Conclusion and recommendations: This study showed that Justicia flava and Tephrosia vogelii possess antimicrobial activity and are therefore potential candidates for combating bacterial infections, especially those accelerated by S. aureus, P. aeruginosa, and Salmonella species.